Association of structural characteristics with immunostimulatory activity of pectic polysaccharides prepared from Tartary buckwheat sprouts by enzymatic degradation and partial acid hydrolysis - Lin Zhang; Bo Li; Xuan Gao; Mao-Qing Wang; Ya-Nan Cao; Mao-Ling Tan; Yi-Chen Hu; Liang Zou; Dan Li; Yong Deng; Jing-Wei Huang; Ding-Tao Wu (Food Research International, 2026)

Projected runoff responses to climate and vegetation changes on the Tibetan Plateau - Bo Feng; Xianhong Meng; Xianyu Yang; Mingshan Deng; Lin Zhao; Zhaoguo Li; Shaoying Wang (Atmospheric Research, 2026)

The impact of low ambient pressure on the cavitation erosion intensity of aluminum alloy materials - Jian-Bo Li; Yong Xia; Wei-Lin Xu; Jun Deng; Jun Chen; Zhen-Yu Du (Ocean Engineering, 2026)

A 44-min periodic radio transient in a supernova remnant - Di Li; Mao Yuan; Lin Wu; Jingye Yan; Xuning Lv; Chaowei Tsai; Pei Wang; Jiaqi Zhao; Weiwei Zhu; Li Deng; Ailan Lan; Renxin Xu; et al. (Science Bulletin, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Andrographolide induces testicular damage by triggering ferroptosis in Sertoli cells via disruption of β-TrCP-mediated ATF4 ubiquitination and degradation - Jiaqi Li; Zhengxin Lu; Nan Zhang; Xiaowei Zhou; Yuanbiao Ma; Jia-qi Li; Yimu Zhang; Zhewen Deng; Na Lin; Peng Yue; Yilin Yang; Qi Zhang; et al. (Chemico-Biological Interactions, 2026)

Genetic regulation of insulin resistance surrogate index (TyG) and susceptibility to common diseases based on phenome-wide association study - Jia-Xin Wu; Ling-Huan Bu; Pei He; Ming-Hui Xia; Lin Bo; Fei-Yan Deng; Shu-Feng Lei (Molecular and Cellular Biochemistry, 2026)

Non-progressive orogenesis of the Southern Tibetan Plateau - Xiaoyu Guo; Hengcheng Ying; Lin Chen; Rui Gao; Xiaofan Deng; Zhanwu Lu; Hongda Liang; Bo Xiang; Michael Murphy; Wenhui Li; Xiao Xu (Science Bulletin, 2026)

The emerging role of high-throughput proteomics in advancing precision medicine - Jia You; Yue-Ting Deng; Luo Chen; Lin-Bo Wang; Yu Guo; Ze-Yu Li; Jian-Feng Feng; Jin-Tai Yu; Wei Cheng (Science Bulletin, 2026)

School greenspace and myopia incidence and burden in Chinese children and adolescents: The Guangzhou children and adolescents cohort study - Xiao-Qi Zhu; Yi Sun; Rong Lin; Ya-Na Luo; Jia-Xin Li; Yi-Dan Zhang; Michael S. Bloom; Matthew H.E.M. Browning; Sam SS. Lau; Shu-Jun Fan; Zhi-Qi Li; Ming-Deng Xiang; et al. (Environmental Research, 2026)

The interplay between antihypertensive medication and lifestyle with cardiovascular outcomes in patients with hypertension: the PURE-China study - Biyan Wang; Zhiguang Liu; Tong Bu; Sumathy Rangarajan; Qiuyan Ma; Xiaocong Li; Qi Qiu; Yang Lin; Lap Ah Tse; Bo Hu; Salim Yusuf; Qiujing Cai; et al. (EPMA Journal, 2026)

ASSR-mediated sludge yield reduction couples deterministic enrichment of Nitrospira with metabolic resource partitioning - Huanzhong Deng; Junling Yang; Ruohong Li; Kewen Li; Hui Lu; Bing Lin; Xingquan Xu; Jiajun Liao; Congrong Ye; Jie Deng; Bo Wu; Lianpeng Sun (Water Research, 2026)

Two birds with one stone: Constructing confined N-doped carbon catalysts to boost solar-driven interfacial water evaporation and peroxymonosulfate mediating antibiotic wastewater purification - Qi-E Zhang; Lin-Bo Deng; Hui-Qing Lv; Guo-Qing Zhao; Yan Pan; Jin Zou; Meng-Ting He; Xun-Kuan Ye; Jin-Gang Yu; Limin Lu (Environmental Research, 2026)

Enhanced marine primary productivity during the long-term Ordovician cooling: A barium isotope perspective from South China - Shengchao Yang; Junxuan Fan; Chao Li; Yi-Bo Lin; Yiying Deng; Zongyuan Sun; Jian Cao; Shu-zhong Shen (Earth and Planetary Science Letters, 2026)

An R2R3-MYB transcription factor TgMYB44 positively regulates petal senescence by enhancing ABA biosynthesis in tulip - Haipo Yang; Yikun Wu; Chengxiao Yuan; Hongqing Yin; Lin Xiang; Xuewei Wu; Honglin Deng; Bo Sun; Zhulong Chan; Yanping Wang (Plant Cell Reports, 2026)

Therapeutic Mechanisms of Stem Cell–Derived Exosomes for Neurological Disorders: An Overview - Congying Lin; Lixin Qi; Xiuying Gao; Lei Hu; Bo Qian; Yixuan Deng; Chunting Zhou; Chenyi Wang; Guanhao Liu; Qiang Ding; Zhenlang Lin; Xuwei Zhu; et al. (Molecular Neurobiology, 2026)

A computationally driven screening-construction-mechanism strategy of magnetic molecularly imprinted polymers for aliphatic aldehydes detection - Yongqing Zhang; Xiaolong Shang; Jiaqi Guo; Ling Ao; Caihong Shen; Miao Liu; Feng Lin; Wenxian Li; Liqiang Zhang; Baoguo Sun; Wei Dong; Xiaotao Sun; et al. (Food Chemistry, 2025)

Application of nanomaterials in central nervous system disorders - Yixuan Deng; Yani Feng; Bangming Ye; Lei Hu; Lixin Qi; Chenyi Wang; Chunting Zhou; Guanhao Liu; Xiuying Gao; Congying Lin; Qiang Ding; Ziming Zhao; et al. (Psychopharmacology, 2025)

A copper-based single-atom material effectively controls plant diseases with nearly zero soil residue and low phytotoxicity - Rui Huang; Yong Yan; Yafei Jiang; Chunyan Gu; Zhentao Ma; Lifang Xue; Yao Ma; Xingen Lin; Juan Zhang; Ran Shi; Yiwen Wang; Linjing Liu; et al. (Science Bulletin, 2025)

Linkage site regulation on photocatalytic hydrogen evolution performance of naphthalene-based conjugated polymers - Xufeng Ji; Nan Chen; Jinlian Yuan; Ao Sun; Lin Zhou; Xing Ding; Yi Yang; Bo Chai; Deng Ding; Xiaohu Zhang; Ke Dai; Hao Chen (Chemical Engineering Journal, 2025)

Maternal transcription factor OTX2 directly induces SETD1A and promotes embryonic genome activation in human pre-implantation embryos - Tianlei Zhang; Ziyan Peng; Fei Meng; Zhuo Li; Junru Chen; Qinwei Zhou; Lizhi Leng; Hao Bo; Guangxiu Lu; Yun Deng; Feng Gu; Ge Lin (Science China Life Sciences, 2025)

Epigenetics in the modern era of crop improvements - Yan Xue; Xiaofeng Cao; Xiangsong Chen; Xian Deng; Xing Wang Deng; Yong Ding; Aiwu Dong; Cheng-Guo Duan; Xiaofeng Fang; Lei Gong; Zhizhong Gong; Xiaofeng Gu; et al. (Science China Life Sciences, 2025)
Epigenetic mechanisms are integral to plant growth, development, and adaptation to environmental stimuli. Over the past two decades, our comprehension of these complex regulatory processes has expanded remarkably, producing a substantial body of knowledge on both locus-specific mechanisms and genome-wide regulatory patterns. Studies initially grounded in the model plant Arabidopsis have been broadened to encompass a diverse array of crop species, revealing the multifaceted roles of epigenetics in physiological and agronomic traits. With recent technological advancements, epigenetic regulations at the single-cell level and at the large-scale population level are emerging as new focuses. This review offers an in-depth synthesis of the diverse epigenetic regulations, detailing the catalytic machinery and regulatory functions. It delves into the intricate interplay among various epigenetic elements and their collective influence on the modulation of crop traits. Furthermore, it examines recent breakthroughs in technologies for epigenetic modifications and their integration into strategies for crop improvement. The review underscores the transformative potential of epigenetic strategies in bolstering crop performance, advocating for the development of efficient tools to fully exploit the agricultural benefits of epigenetic insights.

Investigating the main contributors to esterification activity and identifying the aqueous-phase ester synthases in Daqu - Yu Tie; Lin Wang; Bo Ding; Zhao Deng; Qian Yang; Min Zhu; Zhengyun Wu; Lan Tang; Taikei Suyama; Wenxue Zhang (Food Bioscience, 2025)

Activation of persulfates on carbon nanotubes for water decontamination: Is the non-radical process consistently considered across different pH levels? - Jiali Peng; Lun Li; Shihuai Deng; Hongyu Zhou; Yanjun Li; Chenye Fu; Long Lin; Yue Yuan; Wei Wei; Guochun Lv; Gang Yang; Xiaohui Lu; et al. (Journal of Hazardous Materials, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Plasma proteomics identifies proteins and pathways associated with incident depression in 46,165 adults - Jujiao Kang; Liu Yang; Tianye Jia; Wei Zhang; Lin-Bo Wang; Yu-Jie Zhao; Jia You; Yue-Ting Deng; Yi-Jun Ge; Wei-Shi Liu; Yi Zhang; Yi-Lin Chen; et al. (Science Bulletin, 2025)

A sustainable process for Pb, Zn, and Fe from copper slag by salt roasting-magnetization roasting-magnetic separation - Xinze Gao; Yinhe Lin; Dong Guan; Zhaohua Liu; Bo Deng; Qingshan Du; Yanjun Liu; Sen Yu; Juncheng Li; Lingling Cao (Process Safety and Environmental Protection, 2025)

Concentric Compressive Behavior and Design of Stainless Steel–Concrete Double-Skin Composite Tubes Influenced by Dual Hydraulic Pressures - Jian-Tao Wang; Yang Yang; Kai-Lin Yang; Deng-Long Hu; Long-Bo Xu; Jun-Xin Li (Journal of Marine Science and Engineering, 2024)
The external hydraulic pressure and internal medium pressure acting on submarine pipelines can lead to the coupling effect of active and passive constraints on the mechanical performance of steel–concrete double-skin composite tubes, resulting in a significantly different bearing capacity mechanism compared to terrestrial engineering. In this paper, the full-range concentric compressive mechanism of new-type stainless steel–concrete double-skin (SSCDS) composite tubes subjected to dual hydraulic pressure was analyzed by the finite element method. The influence of geometric–physical parameters at various water depths was discussed. The key results reveal that imposing dual hydraulic pressures significantly improves the confinement of double-skin tubes to encased concrete, resulting in a higher axial compressive strength and a non-uniform stress distribution; increasing the material strengths of concrete, outer tubes and inner tubes results in an approximately linear enhancement in axial bearing capacity; enhancing the diameter-to-thickness ratios of outer tubes and inner tubes can decrease the bearing capacity of SSCDS composite tubes; and the axial compression strength of SSCDS composite tubes with a higher hollow ratio of 0.849 tends to decrease with increasing outer hydraulic pressure. A practical method that integrates the effects of dual hydraulic pressures was developed and validated for the strength calculation of SSCDS composite tubes. This research provides fundamental guidelines for the application of pipe-in-pipe structures in deep-sea engineering.

New insights into the chemotaxonomic implications of diterpenoid alkaloid composition in Aconitum sessiliflorum - Jing-chuan Wu; Pei-xin Deng; Bo Yang; Yi-xuan Guan; Shuai Huang; Lin Chen; Xian-li Zhou (Biochemical Systematics and Ecology, 2024)

Nanotechnology-based optical sensors for Baijiu quality and safety control - Wei Dong; Zhen Fan; Xiaolong Shang; Mengjun Han; Baoguo Sun; Caihong Shen; Miao Liu; Feng Lin; Xiaotao Sun; Yanfei Xiong; Bo Deng (Food Chemistry, 2024)

Effect of an air bubble on the collapse shock wave of a cavitation bubble - Jian-Bo Li; Wei-Lin Xu; Yong Xia; Mao Ye; Yan-Wei Zhai; Jun Deng (Ocean Engineering, 2024)

Association between Baijiu chemistry and taste change: Constituents, sensory properties, and analytical approaches - Wei Dong; Xinran Dai; Yintao Jia; Siting Ye; Caihong Shen; Miao Liu; Feng Lin; Xiaotao Sun; Yanfei Xiong; Bo Deng (Food Chemistry, 2024)

High resolution osteoclast-targeted imaging-guided osteoporosis alleviation via persistent luminescence nanocomposite - Xiao Lin; Kewen Zhang; Yang Li; Fang Nan; Jun Li; Hui Zhang; Wei Deng; Weihang Ding; Kaixuan Li; Nur Jarhen; Yitong Zhou; Xiao Yu; et al. (Chemical Engineering Journal, 2024)

Virgin coconut oil: A comprehensive review of antioxidant activity and mechanisms contributed by phenolic compounds - Yu-Qing Zeng; Jin-Tao He; Bo-Yong Hu; Wen Li; Jing Deng; Qin-Lu Lin; Yong Fang (Critical Reviews in Food Science and Nutrition, 2024)

Numerical simulation method and deterioration analysis of load-bearing performance of tunnel linings containing cold joints in plain concrete - Huang-Shi Deng; He-Lin Fu; Yi-Min Wu; Yi-Bo Zhao; Hai-Dong Yi (Tunnelling and Underground Space Technology, 2024)

Undescribed matrine-type alkaloids from Sophora alopecuroides with anti-inflammatory activity - Ding Luo; Jia-Wen Zou; Jing-Hao Wang; He Tian; Hua-Yan Xie; Tian-Xi Zhu; Hui-Hui Zhu; Lu-Ming Deng; Chun-Lin Fan; Hao Wang; Guo-Cai Wang; Yu-Bo Zhang (Phytochemistry, 2024)

Co-infections of Aeromonas dhakensis and Chryseobacterium indologenes in largemouth bass (Micropterus salmoides) - Qin Yang; Yun-Yao Tu; Na Zhang; Bo Miao; Yu-Zhou Zhang; Xun-Teng Deng; Tao He; Sheng-Qi Su; Ling-Yun Lin; Song Zhu (Aquaculture, 2024)

Effects of land-use patterns on seasonal water quality at multiple spatial scales in the Jialing River, Chongqing, China - Yuan-Bo Wang; Muhammad Junaid; Jiao-Yun Deng; Qi-Ping Tang; Lin Luo; Zhuo-Yuan Xie; De-Sheng Pei (CATENA, 2024)

An integrated mycotoxin-mitigating agent can effectively mitigate the combined toxicity of AFB1, DON and OTA on the production performance, liver and oviduct health in broiler breeder hens - Meng-Ling Ruan; Jie Wang; Zhi-Yuan Xia; Xue-Wu Li; Bo Zhang; Guan-Lin Wang; Yuan-Yuan Wu; Yanming Han; Jiang Deng; Lv-Hui Sun (Food and Chemical Toxicology, 2023)

Two new triterpenoid saponins from Bupleurum marginatum Wall. ex DC - Ke Luo; Rong-Ji Dai; Zhi Wang; Yan-Bo Zeng; Yu-Lin Deng; Fang Lv (Natural Product Research, 2023)

Schizophrenia in the genetic era: a review from development history, clinical features and genomic research approaches to insights of susceptibility genes - Ye Lv; Lin Wen; Wen-Juan Hu; Chong Deng; Hui-Wen Ren; Ya-Nan Bao; Bo-Wei Su; Ping Gao; Zi-Yue Man; Yi-Yang Luo; Cheng-Jie Li; Zhi-Xin Xiang; et al. (Metabolic Brain Disease, 2023)

Recent advances in micro (nano) plastics in the environment: Distribution, health risks, challenges and future prospects - Yan-Bo Ma; Zhuo-Yuan Xie; Naima Hamid; Qi-Ping Tang; Jiao-Yun Deng; Lin Luo; De-Sheng Pei (Aquatic Toxicology, 2023)

Point defect engineering of elemental phosphorus for photocatalytic hydrogen evolution - Yajie Sun; Xinya Pei; Bo Wang; Yun Hau Ng; Ruixue Zhu; Qichao Zhang; Jiguang Deng; Yuxi Liu; Lin Jing; Hongxing Dai (Chemical Engineering Journal, 2023)

Reducing the background interference of liquid–liquid extraction method during Baijiu aroma analysis - Wei Dong; Wenxuan Lin; Xiaoman Chen; Xudong Lian; Caihong Shen; Miao Liu; Feng Lin; Xiaotao Sun; Youqiang Xu; Yanfei Xiong; Bo Deng (Food Chemistry, 2023)

Atmospheric chemistry of nitrous acid and its effects on hydroxyl radical and ozone at the urban area of Beijing in early spring 2021 - Wenqian Zhang; Shengrui Tong; Deng Lin; Fangjie Li; Xinran Zhang; Lili Wang; Dongsheng Ji; Guiqian Tang; Zirui Liu; Bo Hu; Maofa Ge (Environmental Pollution, 2023)

Measuring students’ exposure to particulate matter (PM) pollution across microenvironments and seasons using personal air monitors - Ian Ryan; Xinlei Deng; George Thurston; Haider Khwaja; Xiaobo Romeiko; Wangjian Zhang; Tia Marks; Bo Ye; Shao Lin (Environmental Monitoring and Assessment, 2023)

Immunotherapies for the Effective Treatment of Primary Autoimmune Cerebellar Ataxia: a Case Series - Jiao Li; Bo Deng; Wenli Song; Keru Li; Jingwen Ai; Xiaoni Liu; Haocheng Zhang; Yi Zhang; Ke Lin; Guofu Shao; Chunfeng Liu; Wenhong Zhang; et al. (The Cerebellum, 2022)

Ammonium Removal by a Newly Isolated Heterotrophic Nitrification–Aerobic Denitrification Bacteria Pseudomonas Stutzeri SDU10 and Its Potential in Treatment of Piggery Wastewater - Lifei Chen; Jianqiang Lin; Deng Pan; Yilin Ren; Juan Zhang; Bo Zhou; Linxu Chen; Jianqun Lin (Current Microbiology, 2020)

Gastrointestinal involvement of COVID-19 and potential faecal transmission of SARS-CoV-2 - Min Song; Zong-lin Li; Ye-jiang Zhou; Gang Tian; Ting Ye; Zhang-rui Zeng; Jian Deng; Hong Wan; Qing Li; Jin-bo Liu (Journal of Zhejiang University-SCIENCE B, 2020)

Enhanced Biosorption of Sb(III) onto Living Rhodotorula mucilaginosa Strain DJHN070401: Optimization and Mechanism - Chang-sheng Jin; Ren-jian Deng; Bo-zhi Ren; Bao-lin Hou; Andrew S. Hursthouse (Current Microbiology, 2020)

An overview of COVID-19 - Yu Shi; Gang Wang; Xiao-peng Cai; Jing-wen Deng; Lin Zheng; Hai-hong Zhu; Min Zheng; Bo Yang; Zhi Chen (Journal of Zhejiang University-SCIENCE B, 2020)

Two-factor ANOVA of SSH and RNA-seq analysis reveal development-associated Pi-starvation genes in oilseed rape - Zhong-Wei Zhang; Ling-Yang Feng; Jian-Hui Wang; Yu-Fan Fu; Xin Cai; Chang-Quan Wang; Jun-Bo Du; Ming Yuan; Yang-Er Chen; Pei-Zhou Xu; Ting Lan; Guang-Deng Chen; et al. (Planta, 2019)

An Experimental Investigation of the Failure Mechanisms of Jointed and Intact Marble under Compression Based on Quantitative Analysis of Acoustic Emission Waveforms - Zheng-Hu Zhang; Jian-Hui Deng; Jian-Bo Zhu; Lin-Rui Li (Rock Mechanics and Rock Engineering, 2018)

Correction to: Gender difference in acquired seizure susceptibility in adult rats after early complex febrile seizures - Yun-Jian Dai; Zheng-Hao Xu; Bo Feng; Ceng-Lin Xu; Hua-Wei Zhao; Deng-Chang Wu; Wei-Wei Hu; Zhong Chen (Neuroscience Bulletin, 2018)

Correlation analyses revealed global microRNA–mRNA expression associations in human peripheral blood mononuclear cells - Lan Wang; Jiang Zhu; Fei-Yan Deng; Long-Fei Wu; Xing-Bo Mo; Xiao-Wei Zhu; Wei Xia; Fang-Fei Xie; Pei He; Peng-Fei Bing; Ying-Hua Qiu; Xiang Lin; et al. (Molecular Genetics and Genomics, 2018)

Development of a stable Japanese encephalitis virus replicon cell line for antiviral screening - Qiu-Yan Zhang; Xiao-Dan Li; Si-Qing Liu; Cheng-Lin Deng; Bo Zhang; Han-Qing Ye (Archives of Virology, 2017)

Comparison of infrared canopy temperature in a rubber plantation and tropical rain forest - Qing-Hai Song; Yun Deng; Yi -Ping Zhang; Xiao-Bao Deng; You-Xing Lin; Li-Guo Zhou; Xue-Hai Fei; Li-Qing Sha; Yun-Tong Liu; Wen-Jun Zhou; Jin-Bo Gao (International Journal of Biometeorology, 2017)

Integrative multi-omics analysis revealed SNP-lncRNA-mRNA (SLM) networks in human peripheral blood mononuclear cells - Wei Xia; Xiao-Wei Zhu; Xin-Bo Mo; Long-Fei Wu; Jian Wu; Yu-Fan Guo; Ke-Qin Zeng; Ming-Jun Wang; Xiang Lin; Ying-Hua Qiu; Lan Wang; Pei He; et al. (Human Genetics, 2017)

Environmental and cortisol-mediated control of Ca2+ uptake in tilapia (Oreochromis mossambicus) - Chia-Hao Lin; Wei-Chun Kuan; Bo-Kai Liao; Ang-Ni Deng; Deng-Yu Tseng; Pung-Pung Hwang (Journal of Comparative Physiology B, 2016)

Functional relevance for multiple sclerosis-associated genetic variants - Xiang Lin; Fei-Yan Deng; Xing-Bo Mo; Long-Fei Wu; Shu-Feng Lei (Immunogenetics, 2015)

Gender difference in acquired seizure susceptibility in adult rats after early complex febrile seizures - Yun-Jian Dai; Zheng-Hao Xu; Bo Feng; Ceng-Lin Xu; Hua-Wei Zhao; Deng-Chang Wu; Wei-Wei Hu; Zhong Chen (Neuroscience Bulletin, 2014)

Genes in the serotonin pathway are associated with bipolar affective disorder in a Han Chinese population - Bo Xiang; Zhenxing Yang; Yin Lin; Lijie Guan; Xuan Li; Wei Deng; Zeyu Jiang; Guohui Lao; Qiang Wang; Xiaoyu Hao; Xiang Liu; Yingcheng Wang; et al. (Neuroscience Bulletin, 2014)

A novel single-tailed fusiform Sulfolobus virus STSV2 infecting model Sulfolobus species - Susanne Erdmann; Bo Chen; Xiaoxing Huang; Ling Deng; Chao Liu; Shiraz A. Shah; Sven Le Moine Bauer; Carlos León Sobrino; Haina Wang; Yunlin Wei; Qunxin She; Roger A. Garrett; et al. (Extremophiles, 2014)

Comparative study on debris flow initiation in limestone and sandstone spoil - Ning-sheng Chen; Yang Lu; Ming-feng Deng; Da-wei Han; Hai-bo Zhou; Cheng-lin Yang (Journal of Mountain Science, 2013)

Molecular tagging of a stripe rust resistance gene in Aegilops tauschii - Lin Huang; Lian-Quan Zhang; Bao-Long Liu; Ze-Hong Yan; Bo Zhang; Huai-Gang Zhang; You-Liang Zheng; Deng-Cai Liu (Euphytica, 2011)

The effect of excess expression of GFP in a novel heart-specific green fluorescence zebrafish regulated by nppa enhancer at early embryonic development - Wen Huang; Yun Deng; Wei Dong; Wuzhou Yuan; Yongqi Wan; Xiaoyan Mo; Yongqing Li; Zequn Wang; Yuequn Wang; Karen Ocorr; Bo Zhang; Shuo Lin; et al. (Molecular Biology Reports, 2011)

Over-expression of the AtGA2ox8 gene decreases the biomass accumulation and lignification in rapeseed (Brassica napus L.) - Xiao-ying Zhao; Deng-feng Zhu; Bo Zhou; Wu-sheng Peng; Jian-zhong Lin; Xing-qun Huang; Re-qing He; Yu-hong Zhuo; Dan Peng; Dong-ying Tang; Ming-fang Li; Xuan-ming Liu (Journal of Zhejiang University-SCIENCE B, 2010)

Expression analysis of the NDRG2 gene in mouse embryonic and adult tissues - Xiao-Lan Hu; Xin-Ping Liu; Yan-Chun Deng; Shu-Xin Lin; Lin Wu; Jian Zhang; Li-Feng Wang; Xiao-Bin Wang; Xia Li; Lan Shen; Yuan-Qiang Zhang; Li-Bo Yao (Cell and Tissue Research, 2006)